Combined use of arginase II inhibitors and tadalafil for the correction of monocrotaline pulmonary hypertension - Ivan S. Koklin; Lyudmila M. Danilenko (Research Results in Pharmacology, 2019)
Introduction: The concept of the regulatory role of endothelium in the pathogenesis of pulmonary hypertension (PH) is fundamental.